2009
DOI: 10.1021/es901723c
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Chromium(VI) by a Methane-Oxidizing Bacterium

Abstract: Methane-oxidizing bacteria are ubiquitous in the environment and are globally important in oxidizing the potent greenhouse gas methane. It is also well recognized that they have wide potential for bioremediation of organic and chlorinated organic pollutants, thanks to the wide substrate ranges of the methane monooxygenase enzymes that they produce. Here we have demonstrated that the well characterized model methanotroph Methylococcus capsulatus (Bath) is able to bioremediate chromium(VI) pollution over a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(56 citation statements)
references
References 38 publications
4
52
0
Order By: Relevance
“…Kemner et al (18) reported that the speciation of chromium associated with Pseudomonas fluorescens cells was consistent with association of Cr(III) with a phosphoryl functional group. A recent study showed reduction of Cr(VI) to Cr(III) by methane-oxidizing bacteria, a ubiquitous group of environmental bacteria (2). EXAFS analysis showed that Methylococcus capsulatus-associated chromium predominantly existed as Cr(III) and most likely associated with phosphate groups.…”
Section: Discussionmentioning
confidence: 99%
“…Kemner et al (18) reported that the speciation of chromium associated with Pseudomonas fluorescens cells was consistent with association of Cr(III) with a phosphoryl functional group. A recent study showed reduction of Cr(VI) to Cr(III) by methane-oxidizing bacteria, a ubiquitous group of environmental bacteria (2). EXAFS analysis showed that Methylococcus capsulatus-associated chromium predominantly existed as Cr(III) and most likely associated with phosphate groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that methanotrophs also influence the speciation and bioavailability of metals in the environment (Choi et al 2006;Jenkins et al 1994). Hasin et al (2010) have reported the reductive transformation of soluble and more toxic Cr(VI) into a less toxic Cr(III)species by methanotrophic bacteria (Methylococcus capsulatus Bath), as the Cr(III) is insoluble and tends to get precipitated at high pH.…”
Section: Remediation Of Heavy Metals By Methanotrophsmentioning
confidence: 99%
“…Therefore, mb might be particularly critical for ecological success of methanotrophs in such metal-polluted environments where proteins like methanobactin (mb) allow the selective acquisition of Cu, while protecting the methanotrophs against other similar potentially toxic metals. Microbial-based bioremediation of heavy metals, produced from metal plating, tanning, paper-making industries (Cervantes et al 2001;Hasin et al 2010;Zayed and Terry 2003), can be used for detoxification of metals through their conversion to less toxic and less soluble form like Cr(III). Hasin et al (2010) reported a well characterized model of methanotroph Methylococcus capsulatus (Bath), capable of bioremediation of chromium (VI) pollution over a wide range of concentrations (1.4-1,000 mg L -1 of Cr 6?…”
Section: Remediation Of Heavy Metals By Methanotrophsmentioning
confidence: 99%
See 2 more Smart Citations